Pengembangan Layanan Bimbingan Karir Melalui Media Dartboard Tentang Eksplorasi Karir - Ilham Wijayanto; Agungbudiprabowo Agungbudiprabowo (JURKAM: Jurnal Konseling Andi Matappa, 2022)
The purpose of this study is to develop career guidance services through the Dart Board media about career exploration that can be used by guidance and counseling teachers as a medium in providing services. The type of research used in this research is research and development (RnD) using the Borg and Gall development model to the 5th stage, namely design revision by conducting validation tests with material experts, media experts, and guidance and counseling service experts. The data analysis technique used was simple descriptive statistics. The results obtained from the validation test of the development of career guidance services through the dart board media regarding career exploration are the material validation test getting a score of 83.3 in the very good category, the media validation test getting a score of 85 in the very good category, and the validation test for guidance and counseling services getting score 95 with very good category. Therefore, based on the assessment of material experts, media experts, and guidance and counseling service experts, the media dart board on career exploration for students of SMP Muhammadiyah 1 Bambanglipuro is declared feasible to use. The results of the study can be used as a BK teacher as an alternative media in providing career guidance services about understanding career exploration for students.